Mechanisms of stent thrombosis analysed by optical coherence tomography: insights from the national PESTO French registry - Souteyrand, Geraud; Amabile, Nicolas; Mangin, Lionel; Chabin, Xavier; Meneveau, Nicolas; Cayla, Guillaume; Vanzetto, Gerald; Barnay, Pierre; Trouillet, Charlotte; Rioufol, Gilles; Rangé, Gregoire; Teiger, Emmanuel; et al. (European heart journal, 2016)
Angiography has limited value for identifying the causes of stent thrombosis (ST). We studied a large cohort of patients by optical coherence tomography (OCT) to explore ST characteristics and mechanisms. A prospective multicentre registry was screened for patients with confirmed ST. Optical coherence tomography was performed after initial intervention to the culprit lesion (in 69% of cases in a deferred procedure). Stent thrombosis was classified as acute (AST), sub-acute (SAST), late (LST), and very late (VLST). Optical coherence tomography records were analysed in a central core lab. The analysis included 120 subjects aged 61.7 [51.4-70.7]; 89% male. Very late ST was the clinical presentation in 75%, LST in 6%, SAST in 15%, and AST in 4% of patients. Bare metal stents (BMS) were used in 39%, drug-eluting stents (DES) in 59% and bioresorbable vascular scaffolds in 2% of the cases. Optical coherence tomography identified an underlying morphological abnormality in 97% of cases, including struts malapposition (34%), neoatherosclerotic lesions (22%), major stent underexpansion (11%), coronary evagination (8%), isolated uncovered struts (8%), edge-related disease progression (8%), and neointimal hyperplasia (4%). Ruptured neoatherosclerotic lesions were more frequent with BMS than with DES (36 vs. 14%, P = 0.005), whereas coronary evaginations were more frequent with DES than with BMS (12 vs. 2%, P = 0.04). LST + VLST were mainly related to malapposition (31%) and neoatherosclerosis (28%), while prominent mechanisms for AST + SAST were malapposition (48%) and underexpansion (26%). In patients with confirmed ST, OCT imaging identified an underlying morphological abnormality in 97% of cases.